2017
DOI: 10.25196/adcp201712
|View full text |Cite
|
Sign up to set email alerts
|

Induced Abortion among Chinese Women with Living Child-A National Study

Abstract: ObjectiveInduced abortion is widely practiced in China. However, the information on induced abortion is limited. A national cross-sectional survey was designed to determine the risk factors of induced abortion among Chinese women with one child.MethodsWe sampled 16,881 Chinese women with one living child for the study. A structured questionnaire was used to collect induced abortion and related health information. The National Research Institute for Family Planning of China conducted a cross-sectional study amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
3
1
Order By: Relevance
“…The prevalence of induced abortion among precollege students in Ethiopia was observed at 13.6% [ 11 ], which was lower than the findings of the current study. The finding from this study was much higher than the findings in China 8.13% [ 12 ], Cameroon 21% [ 13 ], southern Ethiopia 43.4% [ 14 ], Nigeria 51% [ 15 ], and Northwestern Ethiopia 4.8% [ 16 ]. This variation might be attributed to differences in the time of investigation of sample size, whereas the current finding was almost consistent with the study in Ghana 64% [ 17 ].…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…The prevalence of induced abortion among precollege students in Ethiopia was observed at 13.6% [ 11 ], which was lower than the findings of the current study. The finding from this study was much higher than the findings in China 8.13% [ 12 ], Cameroon 21% [ 13 ], southern Ethiopia 43.4% [ 14 ], Nigeria 51% [ 15 ], and Northwestern Ethiopia 4.8% [ 16 ]. This variation might be attributed to differences in the time of investigation of sample size, whereas the current finding was almost consistent with the study in Ghana 64% [ 17 ].…”
Section: Discussioncontrasting
confidence: 72%
“…In the other study, being in rural areas (OR = 1.21, 95% CI: 1.04–1.39), ages 18-25 (OR = 0.84, 95% CI: 0.72–0.99) and 30 or older (OR = 1.63, 95% CI: 1.42–1.86), and single individuals (OR = 1.72, 95% CI: 1.05–2.83) were more likely to experience induced abortion [ 12 ], where none of the variables showed any statistical association in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast to the trends in Estonia, where the percentage of women having repeat abortions has declined dramatically in recent years [10]. A national cross-sectional survey showed that the prevalence of induced abortion was 8.72% in China between 2006 and 2008 [11]. This study revealed a relatively higher prevalence of induced abortion and repeat abortion in the migrant population than in the general population in China.…”
Section: Discussionmentioning
confidence: 64%
“…A notable percentage increase in the 18–19 age group indicates that attention should be paid to reproductive health education among the youth. Numerous studies have found that married women have a higher incidence of abortion than unmarried women in China [4,11]. The proportion of marriages within the 20–29 age group in the second survey was higher than in the first survey.…”
Section: Discussionmentioning
confidence: 91%